The Involvement of TRP Channels in Bone Homeostasis - Lieben, Liesbet; Carmeliet, Geert (Frontiers in Endocrinology, 2012)
Calcium and bone homeostasis are intimately related. On the one hand, bone relies on a sufficient supply of calcium to maintain its structural and mechanical properties and thus largely depends on calcium absorption in the intestine and calcium reabsorption in the kidney. On the other hand, bone serves as a calcium reserve from which calcium is mobilized to maintain normal calcium levels in blood. A negative external calcium balance will therefore at all times impair skeletal integrity. In addition to the external calcium balance, skeletal homeostasis also depends on the proper differentiation and functioning of bone cells, which relies for a large part on intracellular Ca2+ signaling. Members of the transient receptor potential (TRP) family of ion channels affect skeletal homeostasis by mediating processes involved in the extracellular as well as intracellular Ca2+ balance, including intestinal calcium absorption (TRPV6), renal calcium reabsorption (TRPV5), and differentiation of osteoclasts (TRPV1, TRPV2, TRPV4, TRPV5), chondrocytes (TRPV4) and possibly osteoblasts (TRPV1). In this review, we will give a brief overview of the systemic calcium homeostasis and the intracellular Ca2+ signaling in bone cells with special focus on the TRP channels involved in these processes.